Credit for the Poor: The Experience of Rural Development Scheme of Islami Bank Bangladesh Ltd. - Uddin, Mohammad Main (Journal of Nepalese Business Studies, 2009)
Islami Bank Bangladesh Limited was founded with the major objective of establishing Islamic economy for balanced economic growth by ensuring reduction of rural-urban disparity and equitable distribution of income. In view of the above, Branches of the Bank have been encouraged to invest their deposits in their respective areas and in particular for the economic upliftment of the rural people. Accordingly, a scheme in the name and style of ‘Rural Development Scheme’ has been introduced to cater to the investment needs of the agriculture and rural sector to create opportunity for generation of employment and raising income of the rural people with a view to alleviate poverty. Key words: Islami Bank Bangladesh Ltd (IBBL), Rural Development Scheme (RDS), credit, investment, poor The Journal of Nepalese Business Studies Vol. V, No. 1, 2008, December Page: 62-75